Analisis Pengaruh Marketing Influencer Tiktok Terhadap Keinginan Pembelian Pada Pengguna Aplikasi Tiktok - Ariasih, Made Putri; Putra, I Putu Dharmawan Suryagita Susila (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2022)
The TikTok application contains various videos created by content creators. Content creators whose video content is watched a lot and has many followers are called influencers. Influencers with a large audience usually open services to advertise a product, with influencers the advertised product will be noticed by many people, so that people watching have an intention to buy the advertised product. The purpose of this study was to analyze the influence of the tiktok marketing influencer on the emergence of purchase intentions from users of the tiktok. This study uses a qualitative research approach. The data collection technique used in this study uses data collection techniques on various literature, as well as various reports related to research variables. This study uses data collected by observation techniques on the TikTok. Data was also collected using interview techniques, by interviewing a company that had used the services of an influencer, and interviewing users of the TikTok. This study obtained the results, the first company uses the services of influencers to introduce their products and generate purchase intentions. Second, consumers in making purchasing decisions will seek information about the products they will buy through influencers. Third, video content created by influencers can raise consumers' purchase intention.